Laryngeal Preservation Approaches: Considerations for New Selection Criteria Based on the DeLOS-II Trial - Dietz, Andreas (Front Oncol, 2019)
In the locoregional advanced group of larynx and hypopharyngeal squamous cell carcinomas (LHSCC), there are two kinds of patients: those who are candidates for functional larynx organ preservation (LP) by avoiding ablative surgery and those who are not. Currently, the distinction between them is depending on the patient's needs and desires, the experience and recommendation of the surgeon, the philosophy of the institution and others. The milestone VA trial established non-surgical LP in advanced LHSCC utilizing induction-chemotherapy (IC) with PF (cisplatin, P plus 5-fluorouracil, F) followed by irradiation (IC+RT) as appropriate alternative treatment to total laryngectomy (TL) already in the 1990s. Even thou the VA trial's findings were verified by the EORTC 24891 trial we have an ongoing debate about the best protocol balancing survival and laryngectomy-free survival (LFS) with acceptable late toxicity and good functional outcome. In advanced LHSCC without surgical options preserving the larynx, only IC+RT and primary concurrent chemo-radiotherapy (CRT) are accepted treatment options aiming to preserve a functional larynx. In the US, cisplatin-based CRT is still recommended as best protocol to achieve cure of the disease and LP. But current views on long term survival with functional organ preservation and still high failure rates are addressing the need of better selection of patients which will be discussed as follows taking the current debate in literature and in particular the recently published data of the DeLOS-II trial in consideration.